Cyclo[18]carbon: Insight into Electronic Structure, Aromaticity, and Surface Coupling; Journal of Physical Chemistry Letters; Vol. 21, iss. 10 - Baryshnikov G. V. Gleb Vladimirovich; Valiev R. R. Rashid Rinatovich; Kuklin A. V. Artem Valentinovich; Sundholm D. Dage; Agren H. Hans (2019, 2019)
Title screen